ARE SMALL-SCALE INNOVATIONS BY PARALLEL TEAMS CAPABLE OF ENHANCING ORGANIZATIONAL PERFORMANCE? EMPIRICAL EVIDENCE FROM MALAYSIAN MANAGERS - Maznah Abdullah; Hasnun Anip Bustaman; Nor Halida Haziaton Mohd Noor; Wan Yusrol Rizal Wan Yusof; Siti Maziah Ab. Rahman; Nik Rozhan Nik Ismail, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
Parallel teams such as quality circles have been practiced by many organizations over the past decades to improve their operational performance. The practice, however, does not always produce a desirable result in all organizations. While many organizations from over the world have reported success stories on the practice of parallel team, significant numbers of organizations in Britain and Mexico have disengaged with the practice. Nevertheless, China and Malaysia are still actively endorsing the adoption of parallel team for productivity in various industries. Although the positive impacts of small-scale innovation by parallel teams on operational performance are already clear, its impact on the performance at the organizational level is still vague. To confirm this, 188 managers from 33 Malaysian organizations that actively practicing parallel team for operational performance were involved in the questionnaire-based survey. The results from regression analyses show that the Malaysian managers have a significant belief that innovations by parallel team indeed capable of enhancing performance not only at the operational level, but also to the organizational level. , , , ,